Role of expansin genes in softening of fruits during fruit ripening - ASHA (International Journal of Pharma and Bio Sciences, 2017)
Fruit softening during ripening is a complex process which is associated with various physiological and biochemical changes. These changes include an increase in respiration and ethylene production, de novo synthesis and degradation of pigments and textural changes that result principally from cell wall modification caused by depolymerization and solubilization of cell wall components by various cell wall modifying enzymes which are activated at transcriptional and translational level during fruit softening. However, various molecular and genetic studies suggest that these hydrolases may not be individually responsible for softening and a synergistic action appears to be more plausible for bringing about softening in fruit tissue. The foremost action in this process may be started by a family of proteins known as expansins which probably act by disrupting the hydrogen bonds between cellulose microfibrils and matrix polysaccharides of the cell wall thereby increasing the accessibility of cell wall modifying enzymes. The process of ripening once initiated, continues uncontrolled, leading to excessive softening of the fruit which, in turn, reduces fruit shelf life, makes it susceptible to pathogenic attack and is thus responsible for large-scale post harvest losses. Expansins can be a suitable candidate gene to manipulate ripening in order to increase the shelf life of commercially important fruit crops. This review will focus on a general description of expansins which includes their discovery, mechanism of action, structure and classification, their role in fruit softening during ripening as reported in various fruits and future prospects to use expansins for improvement of fruit crops.